Successful Treatment of Acromegaly and Associated Hypogonadism with First-Line Clomiphene Therapy - Juan D. Palacios; Ricardo J. Komotar; Atil Y. Kargi (Case Reports in Endocrinology)
Clomiphene citrate (CC) has been reported as an effective add-on therapy to somatostatin analogs and dopamine agonists in patients with acromegaly accompanied by hypogonadism; its use as a single agent to treat acromegaly and associated hypogonadism following incomplete surgery has not been previously reported. We report the first case in which clomiphene was utilized as a single agent for the dual management of acromegaly and hypogonadism, not controlled by pituitary surgery alone. The treatment was well tolerated and proved to be effective after a process of treatment withdrawal and reintroduction. We propose that clomiphene may be considered as a cost-effective oral treatment option in select cases of hypogonadal acromegaly.